The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.31559/glm2019.6.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Cartesianization of Complex Forms in Saidou’ Spaces

Abstract: In this work, we propose to define a new space that will be called locally Cartesian space (Saidou'Spaces). It is a space defined by a new topology whose fundamental system of neighborhood are compact cartesian subsets, theses subsets were already defined during our previous work, "Geometrical introduction to Cartesian geometry in complex shapes see [15]. It will have the same properties of a Banach space. Then, we will give the steps of a cartesianization method of complex shapes or region in this space. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The above values were compared with other results from ore-bearing or mining regions of Cameroon [6][7][8][9][10][11][12][13][14][15]. Indoor radon concentrations ranged between 46-143 Bq m −3 in Poli [12], 27-937 Bq m −3 in Lolodorf [15], 88-282 Bq m −3 in Betare-Oya [9], and 31-436 Bq m −3 in the coastal city of Douala [11]. The average values were 82 Bq m −3 , 97 Bq m −3 , 133 Bq m −3 and 139 Bq m −3 , respectively.…”
Section: Indoor Radon Distribution Using Radon Track Detectors (Radtrak)mentioning
confidence: 98%
See 2 more Smart Citations
“…The above values were compared with other results from ore-bearing or mining regions of Cameroon [6][7][8][9][10][11][12][13][14][15]. Indoor radon concentrations ranged between 46-143 Bq m −3 in Poli [12], 27-937 Bq m −3 in Lolodorf [15], 88-282 Bq m −3 in Betare-Oya [9], and 31-436 Bq m −3 in the coastal city of Douala [11]. The average values were 82 Bq m −3 , 97 Bq m −3 , 133 Bq m −3 and 139 Bq m −3 , respectively.…”
Section: Indoor Radon Distribution Using Radon Track Detectors (Radtrak)mentioning
confidence: 98%
“…Saïdou et al [10] previously reported natural radiation exposure to the public in some mining and ore-bearing regions of Cameroon. It has been found that the average inhalation doses due to 222 Rn are 1.5 mSv, 2 mSv, 2.5 mSv and 2.6 mSv in the uranium-bearing region of Poli [12], the uranium and thorium-bearing region Lolodorf [15], the gold mining areas of Betare-Oya [9] and the coastal city of Douala [11], respectively. It can be noted that the above average values are comparable to those found in the current work.…”
Section: Inhalation Dosementioning
confidence: 99%
See 1 more Smart Citation
“…In Cameroon, a total of 450 RADUETs were used to measure indoor radon and thoron concentrations in houses around mining and ore-bearing regions of Poli, Lolodorf, Betare-Oya and Douala [24,[36][37][38][39]. The monitors were hung from the ceiling in the bedroom for two months at a height of 1.…”
Section: Lessons Learned On Radon and Thoron Measurement By The Raduetmentioning
confidence: 99%